SISTEM INFORMASI PENJUALAN RUMAH BERBASIS WEB MENGGUNAKAN PHP DAN MYSQL (Information Technology and Telematics, 2013)
Information Systems home sales by leveraging web technology is a technology sales service and web-based home purchase. In this era craze masyarakt in using the Internet or other online media, the media is more practical and faster to get the information, make online media is widely used in the business sector. The development of information systems based on home sales is made ??easier for homeowners and home seekers to access home buying and selling information. This application uses the methodology of system development life cycle has five stages perancanaan, analysis, design, implementation and evaluation. The programming language used is PHP, using a MySQL database storage. Information systems web-based sales house will feature a home is sold and can be used to look for the home to be purchased. The system will also provide a report to the leader of home sales within a certain timeframe. The benefits of the design of this system is to assist home seekers to obtain home purchase and home sellers in home sales information Keywords: system development life cycle